Sexual Violence Prevention Education for Students at Diniyah Takmiliyah Awaliyah (DTA) Persatuan Umat Islam (PUI) Lemahabang, Cirebon Regency - Yanti Kusnawati; Fika Hidayani (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service was conducted in Lemahabang Wetan Village, Lemahabang District, Cirebon Regency. The primary objective of this initiative was to enhance understanding of reproductive health and to foster awareness about its significance in preventing sexual harassment and communicable diseases. The methodology employed for this community service was the Community-Based Research (CBR) method, which involved collaborative efforts between the local community and an action-oriented team dedicated to community service. This approach employed service learning to advance social movements aimed at achieving greater social justice. The outcomes of this community service initiative revealed a collective concern regarding the issue of violence against children, particularly highlighted during engagements with school principals, teachers, and students. A unified commitment to combat sexual violence against children, with a specific focus on addressing instances occurring within school environments, emerged. The endeavours served to highlight the significance of community engagement and collaborative approaches in fostering safer and healthier communities